MIGRATION PROPERTIES OF KIMBERLITE MINERALS - Afanas'yev V.P.; Babenko V.V. (My University, 1988)
We attempted a new approach to evaluating the migrational ability of minerals, based on their settling rates, one of the fundamental values governing the placer-forming properties of minerals. Since we were interested in the subject primarily for the purpose of elucidating the development and structure of heavy-mineral haloes of kimberlite bodies, we investigated the three principal minerals of kimberlites that make up the haloes, namely, pyrope, picroilmenite, and chrome spinel. The change in the characteristics of heavy-mineral-concentrate haloes governed by the migrational properties of the minerals (concentration per unit volume of sample, grain size spectrum of the heavy-mineral association, relative amounts of heavy and lighter minerals) are exponentially dependent on the transport distance from the bedrock sources. Owing to the vector character and high value of the gradient near the source, these parameters are important prospecting and forecasting features.